2016
DOI: 10.1590/s1806-92902016001200006
|View full text |Cite
|
Sign up to set email alerts
|

Performance and eating behaviour of crossbred goats in Mediterranean climate of Turkey

Abstract: -The objective of the study was to investigate milk yield and eating behaviour of crossbred goats, German Improved Fawn × Hair crossbred (GIF) and Saanen × Hair goats (S), in subtropical eastern Mediterranean climate of Turkey during early summer season. Eight GIF and eight S goats were individually housed in 1.5 × 1.5 m pens. Diurnal eating patterns were monitored by a system that recorded meal size and meal length. Milk yield (kg/day) was 1.77 in GIF and 2.0 in S goats, whereas milk production efficiency (kg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 25 publications
0
15
0
Order By: Relevance
“…For instance, ruminants are active during the day and rest during the night. They protect themselves from extreme environmental factors by means of dissipating body heat by taking advantage of hairlessness of certain body parts, shedding of hair, water restriction, and feed intake [33,34].…”
Section: Small Ruminant Adaptation Mechanisms To Heat Stressmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, ruminants are active during the day and rest during the night. They protect themselves from extreme environmental factors by means of dissipating body heat by taking advantage of hairlessness of certain body parts, shedding of hair, water restriction, and feed intake [33,34].…”
Section: Small Ruminant Adaptation Mechanisms To Heat Stressmentioning
confidence: 99%
“…They have a dynamic eating behavior during warm weather conditions. For example, Fawn goats have different eating behaviors in comparison with Saanen x hair goats, which are exposed to severe heat stress and poor nutritional condition [34]. The authors indicated that Saanen goats had higher meal size and meal length and longer inter-meal interval, meal time, and eating rate within each meal, but a lower number of meals in comparison with German Improved Fawn (GIF) goats.…”
Section: Small Ruminant Adaptation Mechanisms To Heat Stressmentioning
confidence: 99%
“…In the Mediterranean region, the large body of studies about the feeding behavior and diet composition of goats in forest rangelands were mainly conducted in the Northern [12][13][14] and Eastern countries [15][16][17][18]. Limited information is available for the Southern shore of the Mediterranean, which shares similar agro-climatic conditions with the other parts of the Mediterranean but displays specific socio-economic features that impact how grazed herds are managed.…”
Section: Introductionmentioning
confidence: 99%
“…Sample size calculations of eight animals per group were determined based on previous works (32,33,34) , with a statistical power of 0.8. Data (performance, carcass parameters, meat proximate analyses, color measurement and meat FA profile) were statistically analysed as a 2 × 2 factorial arrangement based on a randomized complete block design using PROC MIXED of SAS 9.4 (35) with the following model:…”
Section: Discussionmentioning
confidence: 99%